Effects of overuse of phones and other smart devices on Blepharitis and dry eye (Texas Journal of Medical Science, 2023)
One hundred (100) patients were collected from different hospitals in Iraq, and a cross-sectionalstudy was designed using an electronic system) what is the name of the system) of samples that wereevaluated and approved by the competent committees in Iraq?The population included in the study was residents of Baghdad, Muthanna, and Basrah Governorates whovoluntarily agreed to participate from 5 years to 45 years of age and indicated that those under 18 years ofage should obtain permission from their parents or legal guardians (expressing consent in an e-mail formprior to arrival to the exploratory study).The data collected by in this research, the questionnaire, which was designed based on a number of sections,including the age of patients, in addition to the variables associated with smart phone devices and visualsymptoms to the eyes. Demographic data related to the patients were also analyzed by relying on the IBMSOFT SPSS program.The patients were classified into two groups (60 patients and 40 control). The period of time the patientspent on the phone was 4.3±1.9 for the patient and 3.5±1.1 for the controlin this study, the assessment according to dry eye severity (for mild, 10 (16.6), control 26 (65)-Moderatefor patient 33 (55), control 8 (20)-Severe Irreversible damage to the ocular surface Plus for patient 17 (28.3),control 6 (15) with p-value